DPRD Recess Fund Regulation and Government Governance Problems: A Literature Study on Policy Effectiveness and Its Challenges - Auliya Hanidatul Masdiah; Yunita Sopiana; Deasy Arisanty (International Journal of Science and Society, 2026)
The DPRD recess fund is an important instrument for strengthening political representation and accommodating public aspirations. However, its effectiveness is highly dependent on the quality of regulation and the implementation of good governance principles. This study aims to analyze the legal framework governing DPRD recess funds, examine governance-related problems in their implementation, and assess their effectiveness in enhancing political representation and accountability. This research employs a qualitative method with a literature study approach, utilizing secondary data obtained from laws and regulations, books, and scholarly journals. The findings indicate that the implementation of DPRD recess activities has not fully reflected good governance principles, as evidenced by low public participation, weak transparency and accountability, and suboptimal responsiveness of DPRD members in following up on public aspirations. Furthermore, existing regulations still contain weaknesses in regulating fund utilization and sanctions, which create opportunities for misuse.